(-5/6)+(-5/6) have the same denominator (number at bottom of fraction), so all you have to do is add the numerator(top number). So -5 +-5 =-10 . Now you have -10/6, which simplifies to -5/3.
Hope this helps :)
Answer:
y = 5^x
Step-by-step explanation:
y= b*(a)^x + c
c could = 1 but then you would not have an exponential function. c = 0 because the graph follows the x axis up until x = -2. Suppose c = 1. The the graph would follow y = 1 up until x = - 2
When x = 0, y = 1 which means that b. If b is anything but 0 or 1 then the y intercept would be stretched to a different place. If be = 0 then y would = 0.
So the graph is of the form y = a^x
Now when x = 0 the graph, the y intercept is y = a^0 or y = 1 So the y intercept is (0,1)
Now the next point is thing to solve for is a.
When x = 1, y = 5 (read the graph)
y = a^x
5 = a^1
5 = a because a^1 is a.
Answer
y = 5^x.
5 = a^1
1)V=Ixwxh
=5 cm x 3 cm x 2 cm
=30 cm³
2)V=bxh
=(10m x 6m) x 4m
= 60 m² x4 m
3)V=Ixwxh
=3 cm x 3 cm x 3 cm =27 cm³
=240 m³
I am pretty sure it is 120 or 30